2020
DOI: 10.1101/2020.01.22.20018408
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

microRNA-based predictor for diagnosis of frontotemporal dementia

Abstract: Frontotemporal dementia (FTD) is a heterogeneous neurodegenerative disorder characterized by frontal and temporal lobe atrophy, typically manifesting with behavioural or language impairment. Because of its heterogeneity and lack of available diagnostic laboratory tests there can be a substantial delay in diagnosis. Cell-free, circulating, microRNAs are increasingly investigated as biomarkers for neurodegeneration, but their value in FTD is not yet established. In this study, we investigate microRNAs as biomar… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 184 publications
0
12
1
Order By: Relevance
“…Previous studies have shown the potential of miRNAs in serum, plasma or CSF as diagnostic biomarkers for FTD and ALS, 9 17–20 focussing on comparing healthy controls and patients. However, our findings differ from preceding results: only two miRNAs from our signature (miR-345-5p and miR-200c-3p) were identified as differentially expressed in one of these studies, 20 none in the others. 17–19 Results are conflicting probably due to restricted choices for the analysed miRNAs 17 18 and heterogeneous cohorts, either with sporadic forms 18 19 or a mixture of sporadic and familial forms with different mutations.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Previous studies have shown the potential of miRNAs in serum, plasma or CSF as diagnostic biomarkers for FTD and ALS, 9 17–20 focussing on comparing healthy controls and patients. However, our findings differ from preceding results: only two miRNAs from our signature (miR-345-5p and miR-200c-3p) were identified as differentially expressed in one of these studies, 20 none in the others. 17–19 Results are conflicting probably due to restricted choices for the analysed miRNAs 17 18 and heterogeneous cohorts, either with sporadic forms 18 19 or a mixture of sporadic and familial forms with different mutations.…”
Section: Discussioncontrasting
confidence: 99%
“…Future work will explore longitudinal analyses of plasma miRNAs to assess their use as biomarkers of FTD and ALS progression. Grasso et al 2019 † 19 Magen et al 2020 † 20 This study †…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…On the basis of understanding the miRNA role in motor neuron diseases [11][12][13] and potential discovery of novel biomarkers [20][21][22] , we sought to test the utility of specific miRNAs in the cerebrospinal fluid (CSF) as candidate molecules to predict a positive clinical response to nusinersen in type II/III SMA patients.…”
Section: Introductionmentioning
confidence: 99%